Comparative Study on Indonesian and Philippine Marine Exploitation and The Fish Consumption - Angeles, Roche Christine C.; Mendoza-Dreisbach, Sharon (International Journal of Social Science and Business, 2020)
Indonesia and the Philippines are the two biggest archipelagic countries in the world spanning more than 25,000 islands. This made both states rich in marine natural resources and were considered to be the global centers of marine biodiversity. With the said availability of aquatic resources, both countries have also experienced the exploitation of these assets by people aiming to make profit from overfishing and illegal, unreported, and unregulated fishing practices. As such, the authors saw the merit of exploring the recently-implemented policies of both countries aiming to protect and preserve their marine natural resources. These were vital in assessing its effects on the human consumption of fisheries and triangulating the effectivity and efficiency of the said aquatic-related public policies. This study presented the concrete actions that both Indonesia and the Philippines took to battle illegal poaching by Chinese fishermen in the latter’s waters, prevent the marine exploitation of fishing operations from the former, and the establishment of community-based marine preservations that gave permanent employment to its population and improved their way of living.